1953
DOI: 10.1113/expphysiol.1953.sp001020
|View full text |Cite
|
Sign up to set email alerts
|

The Pituitary Gland and the Vascular Tone of the Kidney

Abstract: IN 1940, one of us and M. Dor investigated in the dog the relationship between renal blood flow, systemic pressure and oxygen consumption in kidneys transplanted in the neck. We found that between 60 and 150 mm. Hg. increase in the blood pressure raised the renal blood flow, but that from about 100 mm. up to 160 mm. there was no relationship between blood pressure and blood flow in the kidney. We concluded that "Pour les reins enerves, les valeurs critiques de pression et de debit veineux sont de l'ordre de 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1957
1957
1977
1977

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The present work reinforces the conclusions of Verney (1926) and of Brull & Louis-Bar (1953) that the posterior lobe of the pituitary provides one or more substances affecting renal blood vessels. They believed vasopressin to be of importance.…”
Section: Dogs With Diabetes Inspidussupporting
confidence: 90%
See 1 more Smart Citation
“…The present work reinforces the conclusions of Verney (1926) and of Brull & Louis-Bar (1953) that the posterior lobe of the pituitary provides one or more substances affecting renal blood vessels. They believed vasopressin to be of importance.…”
Section: Dogs With Diabetes Inspidussupporting
confidence: 90%
“…He concluded that during its passage through the head the blood picked up a substance or substances which inhibited urine flow and decreased renal blood flow, and that the active material(s) came from the pituitary body. Brull & Louis-Bar (1953) also concluded that the pituitary gland contributed a constrictor substance to the blood, and that in its absence the kidney lost its power of auto-regulation and responded almost directly to changes in systemic blood pressure. These observations demand the re-examination of the role of vasopressin in normal animals.…”
Section: Dogs With Diabetes Inspidusmentioning
confidence: 99%
“…It is also established that an injection of adrenaline, by evoking renal vasoconstriction, will improve selective adrenal angiography performed via the renal artery (Kahn 1965) by increasing the blood flow, and further proof of this effect has been reported (Dempster 1973). Since renal vasoconstriction is greatly influenced by the action of vasopressin (Brull and Louis-Bar 1953), it is perhaps significant that in the decerebrate animal adrenal blood flow and hormone production are low (Balfour 1953). On the other hand, in the early morning when vasopressin levels are at their highest, adrenal hormone (cortisol) production is also greatly increased and at its daily maximum including plasma 1-tyrosine levels (Pohorecky and Wurtman 1971) at a time when adrenal blood flow is greatly increased (Doe et al 1956;Sjostrand 1934).…”
Section: Phaeochromocytesmentioning
confidence: 99%
“…The group of normotensives will react with varying Vol.18 No. 4 degrees of reactivity according to the efficiency of the renal-adrenal feed-back system (Fig.1).…”
Section: Vasopressin and Renal Vasotonicitymentioning
confidence: 99%